Determining Grapevine Canopy Effects on Effective Rainfall in Vineyards - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
Rainfall interception was determined for six trellis systems in a vineyard at Stellenbosch. Measurements made directly under the canopy and in the centre of the work row were compared to rainfall measured outside the vineyard. Rainfall was measured over two growing seasons from October until March. There was no difference between rainfall in the centre of the work rows and rainfall outside the vineyard. Due to the effect of seasonal increases in leaf area on rainfall that penetrated through the canopy, rainfall interception was estimated from rainfall measured outside the vineyard, as well as day of season when it occurred by means of multiple linear regressions. Since canopy orientation also influenced the amount of water that reached the soil surface, two regression equations were developed that explained 96% and 89% of the variation in the amount of water that reached the soil surface under slanting and vertical canopies, respectively. On average 86 % and 80 % of the rainfall landed under slanting and vertical canopies, respectively. Based on the assumption that rainfall on the uncovered fraction of the work row was similar to the rainfall measured outside the vineyard, the calculated weighted mean rainfall over the total area did not differ drastically from actual rainfall. This indicated that canopy effects on rainfall interception in vineyards were relatively small.